Strategic Visual Storytelling on Instagram: How Red Communication Indonesia Engages Audiences During Ramadan - Sabila Adinda Puri Andarini; Rizki Anugrah Pratama (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
This research explores the strategic use of visual storytelling by Red Communication Indonesia on Instagram, focusing on their content creation for the popular brand Indomie during the culturally significant month of Ramadan. The research highlights how Instagram's visual-centric platform facilitates emotional connections and enhances audience engagement through culturally relevant narratives. By incorporating particular symbols, the content could resonate with Indonesian Muslim consumers, fostering emotional bonds. The methodology involves qualitative approaches, including semi-structured interviews with key personnels, revealing a focus on visually appealing content and interactive strategies. The findings emphasize the importance of cultural sensitivity, ensuring that the content aligns with Ramadan values while maintaining authenticity. This approach not only enhances engagement but also demonstrates the use of visual storytelling in the digital age.